Research in Great Lakes submerged site archaeology: past, present and future - Sonnenburg, Lisa (Frontiers in Environmental Archaeology, 2025)
This paper is a brief overview of almost two decades worth of research by the author in submerged site archaeology in the Great Lakes basin. This short synopsis will discuss four different sites in and around three Great Lakes representing almost 10,000 years of human occupation. Each site will describe the technology used, the approach toward Indigenous engagement and a summary of results. Presented in chronological order, each project demonstrates the continual technological advancements and resulting reduction in costs associated with researching submerged archaeological sites. In conjunction with illustrating rapid technological change, these projects also show how increasing collaboration with Indigenous communities and integration of traditional knowledge, allow for a more robust interpretation of how humans used these now inundated landscapes over time.